Contrasting metabolic profiles of tasty Andean varieties of tomato fruit in comparison with commercial ones - D’Angelo, Matilde (2018)
BACKGROUND The fruits of most commercial tomato cultivars (Solanum lycopersicum L.) are deficient in flavour. In contrast, traditional ‘criollo’ tomato varieties are appreciated for fruit of excellent organoleptic quality. Small farmers from the Andean valleys in Argentina have maintained their own tomato varieties, which were selected mainly for flavour. This work aims to correlate the chemical composition of the fruit with the sensory attributes of eight heirloom tomato varieties. The long‐term goal is to identify potential candidate genes capable of altering the chemicals involved in flavour. RESULTS A sensory analysis was conducted and the metabolomics of fruit were determined. The data revealed that defined tomato aroma and sourness correlated with citrate and several volatile organic compounds (VOC), such as α‐terpineol, p‐menth‐1‐en‐9‐al, linalool and 3,6‐dimethyl‐2,3,3a,4,5,7a‐hexahydrobenzofuran (DMHEX), a novel volatile recently identified in tomato. Two sensory attributes – sweetness and a not‐acidic taste – correlated with the characteristic tomato taste, and also with fructose, glucose, and two VOCs, benzaldehyde, and 2‐methyl‐2‐octen‐4‐one. CONCLUSIONS These data provide new evidence of the complex chemical combination that induced the flavour and aroma of the good‐tasting ‘criollo’ tomato fruit. That is, the compounds that correlated with defined tomato aroma and acidic taste did not correlate with sweetness, or with characteristic tomato taste.